Sodium Glucose Cotransporter 2 Inhibitors Reduce the Risk of Heart Failure Hospitalization in Patients With Type 2 Diabetes Mellitus: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Zhang, Ailing; Luo, Xufei; Meng, Haiyang; Kang, Jian; Qin, Guijun; Chen, Yaolong; Zhang, Xiaojian (Frontiers in Endocrinology, 2021)
Aim: To evaluate the impact of sodium glucose cotransporter 2 inhibitors (SGLT-2i) on risk of heart failure hospitalization in patients with type 2 diabetes. Methods: We searched the PubMed, Embase, The Cochrane Library, CNKI, Wanfang, CBM and other web knowledge databases for data from randomized controlled trials. We performed statistical analyses by using review Manager (RevMan) 5.3 and STATA 12.0 for meta-analysis. Results: Eight randomized controlled trials that compared SGLT-2i versus placebo met our inclusion criteria and were included in the study. The final meta-analysis included a total of 55763 type 2 diabetes patients. Compared with placebo, SGLT-2i reduced the risk of heart failure hospitalization (RR, 0.63; 95%CI, 0.53 to 0.74; P<0.00001) , MACE (defined as cardiovascular death, myocardial infarction, or ischemic stroke) (RR, 0.92; 95%CI, 0.86 to 0.98; P<0.007), cardiovascular death (RR, 0.78; 95%CI, 0.62 to 0.99; P=0.04) in type 2 diabetes patients. SGLT-2i could reduce the risk of death from any cause (RR, 0.77; 95% CI, 0.59 to 1.01; P=0.06) but without statistical significance in type 2 diabetes patients. Conclusion: Compared with placebo, SGLT-2i may reduce the risk of heart failure hospitalization, MACE and cardiovascular death. Therefore, SGLT-2i may be an ideal choice for type 2 diabetes mellitus patient with heart failure. These results will help inform practitioners, patients, and authorities making appropriate choices in hypoglycemic therapy clinical practice.